Digitally crafting a resistant professional identity: The case of Brazilian 'dirty' bloggers. (November 2018) - Barros, Marcos
We explore how the consequences of disidentification from prevailing professional identities impacted the creation of a new identity and how social media tools enabled and shaped this process. We investigate these phenomena through the struggle of a group of Brazilian journalists who strived to escape the regulation of traditional media identity, creating their own identity as progressive bloggers. Analyzing blog entries and press articles, we uncover four distinctive forms of identity work—historical construction, embracing stigma, establishing authenticity, and satirical deconstruction—fueled by four journalism macro-discourses. Our article contributes to existing literature by uncovering the dynamics of disidentification, its consequences, and identity creation. We also add to the debate on the interaction between identity and resistance by proposing the concept of resistant-identity work, where—beyond being a form or a result of identity work—resistance might enact this process. Finally, we contribute to the study of online-identity processes by demonstrating how the characteristics of social media enable and shape a new form of identity work that is collective and visible.